2020
DOI: 10.22271/chemi.2020.v8.i4f.9715
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of heterosis for yield and yield related traits in okra (Abelmoschus esculentus (L.) Moench)

Abstract: The present study was conducted in okra to estimate the magnitude of heterosis and to identify superior cross combinations for yield and its component traits. Thirty six F1s were developed by crossing 6 lines viz., Pusa Sawani (L1), Parbhani Kranti (L2), Arka Abhay (L3), Arka Anamika (L4), AE 65 (L5) and 14/11 (L6) and 6 testers viz., AE 64 (T1), AE 66 (T2), AE 17 (T3),14/4 (T4), 14/5 (T5) and 14/10 (T6) of okra in line x tester design during summer of 2018. All the 36 F1s along with their 12 parents (6 lines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…Ten out of the 12 crosses showed signifcant positive MP heterosis and 10 crosses for BP heterosis. Similar magnitude of heterosis was also reported by [13,[33][34][35][36][37][38][39].Te best crosses, which were classifed on the basis of heterosis parameters, showed that two out of the 12 studied crosses were derived from P 4 (Line 4.1.18) as male or female parent that was classifed as a good performance for plant height, no. of pods/plant, average weight of pod, total fresh pods, weight of small pods/plot, pods length, pods diameter, and weight of medium pods.…”
Section: Discussionsupporting
confidence: 81%
“…Ten out of the 12 crosses showed signifcant positive MP heterosis and 10 crosses for BP heterosis. Similar magnitude of heterosis was also reported by [13,[33][34][35][36][37][38][39].Te best crosses, which were classifed on the basis of heterosis parameters, showed that two out of the 12 studied crosses were derived from P 4 (Line 4.1.18) as male or female parent that was classifed as a good performance for plant height, no. of pods/plant, average weight of pod, total fresh pods, weight of small pods/plot, pods length, pods diameter, and weight of medium pods.…”
Section: Discussionsupporting
confidence: 81%